(untitled) (Journal of Informatics Education and Research, 2024)
The representation of tribal communities in Indian English literature reflects a rich tapestry of cultural heritage, social struggles, and resilience. This paper explores how Indian English writers have depicted the challenges faced by tribal communities, including displacement, marginalization, and cultural erosion, while also highlighting their resilience through narratives of survival, adaptation, and assertion of identity. Analyzing works by renowned authors, the study underscores how literature has served as a platform for both documenting tribal experiences and fostering empathy among broader audiences. Through a critical examination of selected novels, short stories, and poems, the paper reveals the evolving portrayal of tribal life, emphasizing themes of resistance, identity, and cultural preservation.